Estimation of Genetic Diversity in Bamboos through Metroglyph Analysis - Bhandari, M. S.; Kaushal, R.; Tewari, S. K.; Banik, R. L. (Indian Forester, 2012)
Fourteen species of bamboo were evaluated for nutritional and fodder quality parameters through metroglyph analysis. On the basis of morphological and qualitative variation in bamboo species scatter diagram was prepared. An examination of the scatter diagram revealed that six groups could be distinguished on the basis of morphological variation. All the species were divided into six groups. Maximum number of species was comprised in group-II (5 species) followed by group-V (4 species) and group-IV (2). From metroglyph and index score analysis, long range of index score was from 16 to 22 observed which itself indicated the large amount of variation in the bamboo species studied.